Awake emergency laparotomy under combined spinal epidural anaesthesia in a high-risk patient with severe pulmonary disease and neuromuscular blocking agent anaphylaxis - Shikshya Khatiwoda; Satya Durga Anantapatnaikuni (BMJ Case Reports, 2026)
Bowel obstruction is a prevalent surgical emergency, particularly among the elderly, necessitating prompt intervention. Emergency laparotomy is associated with high morbidity and mortality, particularly in frail elderly patients with multiple comorbidities. General anaesthesia with neuromuscular blockade is standard practice but may be unsuitable in patients with severe respiratory disease or documented anaphylaxis to neuromuscular blocking agents (NMBAs). Neuraxial anaesthesia is not a novel technique, having been established since Bier’s first description of spinal anaesthesia in 1898–1899 and widely adopted in surgical practice long before the introduction of neuromuscular blockade. Nevertheless, its use as the sole anaesthetic technique for emergency laparotomy remains uncommon in modern practice. NMBAs are responsible for approximately 60–70% of anaesthesia-induced hypersensitivity reactions, with rocuronium and succinylcholine being the most frequently implicated agents. Cross-reactivity among NMBAs is well-documented, posing a significant challenge in patients with known allergies . The perioperative management of patients with known NMBA allergies demands meticulous anaesthetic planning to mitigate the risk of adverse reactions while ensuring optimal surgical conditions. Combined spinal–epidural anaesthesia (CSEA) was first introduced by Brownridge in 1981 as an alternative to single-shot spinal or epidural anaesthesia, particularly for caesarean sections. This technique, involving the administration of anaesthetic agents into both the epidural and subarachnoid spaces, was later refined by Coats and Mumtaz et al into the ‘needle-through-needle’ method. We report a case of an awake emergency laparotomy performed under CSEA in a frail elderly patient with severe chronic obstructive pulmonary disease and life-threatening anaphylaxis to multiple NMBAs. Surgery was completed successfully without conversion to general anaesthesia, and the patient had an uncomplicated perioperative course with no respiratory compromise. This case highlights the feasibility of neuraxial anaesthesia as the sole anaesthetic technique in carefully selected high-risk patients undergoing emergency abdominal surgery and underscores the importance of multidisciplinary planning and shared decision-making.